Pojiale: Another side of the Buginese - Kadir, Yahya (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
This paper discusses a unique side of the Bugis that has not received attention in several literatures about the Bugis. The Buginese tends to express himself excessively and aggressively. Local people label such self-expression as pojiale, instead of using siri na pesse (one of the Bugis ethics and cultural values) as the primary reference to describe the character and behavior of the Bugis people, but rather based on the experience and reflection of the author as a Bugis person who was born and grew up in the life of the Buginese. From this experience and reflection, the author finds the pojiale as the unique character possessed by the Bugis. The gap between the ideal values of Bugis culture (Bugis ethics and siri na pesse culture) are factually practiced in the social life of the Bugis.